Levantamento de fitonematóides nas culturas de soja e milho no município de Jataí-Go - Silva, Franciane Gomes da (2007)
Population surveys of plant parasite nematodes are an important tool for the evaluation of their presence and losses caused by these organisms in many crops. The county of Jataí is considered as an important maize and soybean producer. Soybean was introduced in the county in the 80 s and, up to now, a significant increase in planted area and yield has been observed. Ten years ago, the county became a producer of a second maize crop (winter crop) and, since then, reached considerable yield averages and profitability for the region s farmers. However, nematode foci started appearing in the county, and spread slowly, becoming a problem in most fields. Thus, this study surveyed the nematodes in soybean and maize cropping areas in the county of Jataí, GO, in the 2006/2007 agricultural season, and prepared a map with the qualitative and quantitative distribution of the nematodes for subsequent use in control strategies. After analyzing and dividing the county in 20 areas, a sampling scheme was defined and the survey was done from 15 to 22 December 2006. A total of 309 soil and root samples were collected in the county and taken to laboratory for nematode extraction and identification. Of the analyzed, 96.7% were positive for Heterodera glycines. The root lesion nematode, Pratylenchus brachyurus, was found in 77.3% of the samples. The genus Helicotylenchus was present in 47% of the samples, although it is not of primary importance for soybean and maize. There are four races of Heterodera glycines found in the county and, moreover, most of the resistant cultivars available in the market are not resistant to all these races. Maize, as an option for culture rotation to solve the problem of cyst nematode, increases the population of Pratylenchus brachyurus, complicating the management of maize and soybean. There is an urgent need to establish control strategies for the nematodes H. glycines and P. brachyurus in Jataí County . Next step should be mapping the races of Heterodera glycines in the county to potentialize the use of the resistant soybean cultivars.